G6PD deficiency and absence of α‐thalassemia increase the risk for cerebral vasculopathy in children with sickle cell anemia. (30th June 2015) - Joly, Philippe; Garnier, Nathalie; Kebaili, Kamila; Renoux, Céline; Dony, Arthur; Cheikh, Nathalie; Renard, Cécile; Ceraulo, Antony; Cuzzubbo, Daniela; Pondarré, Corinne; Martin, Cyril; Pialoux, Vincent; et al.
Abstract: The aim of this study was to test the association between hematological/genetic factors and cerebral vasculopathy in children with sickle cell anemia (SCA). A group with cerebral vasculopathy (VASC) was composed of children who had stroke ( n  = 6), silent infarct ( n  = 11), or an abnormal transcranial Doppler ( n  = 5). Eighty‐four patients had neither positive history of stroke or silent infarct, nor abnormal transcranial Doppler (NORM group). An intermediate group (COND; n  = 15) was composed of SCA children with a conditional transcranial Doppler. Biological analyses were performed on samples obtained at steady state and before the beginning of any chronic treatment. The comparisons of the three groups demonstrated a protective effect of α‐thalassemia against cerebral vasculopathy through its effects on hemoglobin and reticulocyte levels. Moreover, we observed higher frequency of G6PD deficiency in the VASC group compared with the other groups. Our study confirms the key role of α‐thalassemia and G6PD status in the pathophysiology of cerebral vasculopathy in SCA children.